Poéticas transmasculinas: de Herzer aos dias atuais - Thales Gabriel Trindade de Moura (2024)
The visibility basis of trans men and transmasculine people as social and political identities in Brazil has exponentially increased since the 2000s. The emergence of transmasculinities is mobilized, especially from the country's redemocratization process and the strengthening of movements such as feminism, LGBT and the black movement that made a broad front struggling for their rights. Currently, transmasculine people are building their identities in dialogue with their transcestralities. Existences and memories erased or silenced from history are rescued in several artistic expressions (literature, music, cinema, visual and scenic arts). Thus, based on a comparative work and considering the intersection between Literature, History and Cultural Memory, this research investigates how the visibility basis of transmasculine corporalities is revealed through the enunciative and performative spaces of poetry produced by transmasculinities from Herzer's scenario, in the 80’s, to the present days. The adopted theoretical framework will be permeated by different perspectives of transmasculine theorists and their epistemes, such as Leslie Feinberg (1997); Jamison Green (2006); Jack Halberstam (1998, 2012, 2020) - these in the American context. Furthermore, Paul Preciado (2017, 2018, 2020); Sam Bourcier (2020); Miquel Missé (2018) on the European scenery and Guilherme Almeida (2012, 2021); Simoni Ávila (2014); Benjamin Neves (2020); João Nery (2016, 2017); Leonardo Peçanha (2021); Kaio Lemos (2020) and Bruno Santana (2019) in the Brazilian context. To reflect on gender and sexuality issues, the works of Judith Butler (2019) and Guacira Lopes Louro (2004) will be consulted. For the work of poetic analysis, the thoughts of Antonio Candido (2001; 2006), Audre Lorde (2019) and Tatiana Nascimento (2019) will be adopted. The research, therefore, first attempts to present an overview of transmasculine subjectivity in different historical moments and then demonstrate how the transmasculine bodies experiences are used not only as means of denounce the countless violences and invisibilities suffered, but also as a way of create their memories and reframe their existences in the process of transition through poetry writing.